2017
DOI: 10.1016/j.applthermaleng.2016.07.154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-condensable gas on the startup of a loop heat pipe

Abstract: It is essential to tackle the startup issues prior to the broad application of loop heat pipes (LHPs) in both space and terrestrial surroundings. As non-condensable gas (NCG) is an important factor affecting the startup behavior, its effects on the startup performance of an ammonia-stainless steel LHP with and without preconditioning were experimentally investigated in this work. The temperature overshoot, liquid superheat and startup time were employed as the evaluation criteria. Nitrogen was selected to simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…As a result the condensation rate drops and the performance of the system decrease significantly. This reduction of performance is extensively reported in the literature [6][7][8][9][10][11][12][13][14][15][16][17] and this is also recognized as a challenge of TCM systems under vacuum conditions [5,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 96%
“…As a result the condensation rate drops and the performance of the system decrease significantly. This reduction of performance is extensively reported in the literature [6][7][8][9][10][11][12][13][14][15][16][17] and this is also recognized as a challenge of TCM systems under vacuum conditions [5,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 96%
“…The advantages of the flexibility, temperature control and heat transport capability can make LHPs extend to the applications of terrestrial surroundings, aircraft, submarine and high-speed railway [3][4][5][6]. Over the past two decades, a large number of experimental, theoretical and numerical simulation studies on LHPs have been reported to provide useful data to comprehensively understand the physical mechanisms under various operating conditions and to optimize their design [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the start-up process is complex and heavily depends on the compensation chamber and evaporator construction, initial conditions inside the evaporator, and the operation immediately prior to start up [5]. if the vapour grooves already contain vapour, evaporation will occur once power is applied [5,7]. Secondly, if the evaporator core is filled with liquid, then there is minimum heat transfer from the evaporator to the CC; nonetheless, if vapour is present in the core, heat leak through the primary wick to the CC is increased as discussed in Section 2.3.1.…”
Section: Start-upmentioning
confidence: 99%
“…In addition to the distribution of fluid within the evaporator grooves and evaporator core, the presence of non-condensable gas (NCG) has shown to both degrade the performance of LHPs and affect start-up [7]. Although NCG can be found in almost every part of the system loop, it tends to accumulate in the CC which causes a modification of the system pressure.…”
Section: Start-upmentioning
confidence: 99%
See 1 more Smart Citation